Edukasi Hukum Perlindungan Anak dalam Pencegahan Bullying sebagai Implementasi Program Sekolah Ramah Anak di SMK Negeri 12 Medan - Hendriawan Hendriawan; Jumakir Jumakir; M. Dian Wahyudi (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
Bullying in schools causes serious psychological and academic impacts on students. Legal education on child protection serves as a preventive strategy that can raise students’ awareness of children’s rights and the consequences of bullying, while also supporting the implementation of Child-Friendly School programs. This study aims to examine the effectiveness of legal education on child protection in improving students’ knowledge, attitudes, and behaviors related to bullying at SMK Negeri 12 Medan. The study employed a mixed methods approach with a sequential explanatory design. Quantitative data were collected from 80 students in grades X and XI using questionnaires administered before and after the educational intervention, while qualitative data were obtained through interviews and observations. The legal education was conducted in four structured sessions covering the definition of bullying, children’s rights, behavioral boundaries, and legal sanctions. Quantitative data were analyzed using descriptive statistics and bivariate tests, whereas qualitative data were analyzed thematically. Before the intervention, 56.25% of students lacked knowledge of the Child Protection Law and the consequences of bullying. After the intervention, 62.5% of students demonstrated good knowledge, with a p-value of 0.003 (<0.05), indicating a significant improvement. Observations and interviews revealed increased empathy, social responsibility, and active participation in creating a safe and inclusive school environment. Legal education on child protection effectively enhances students’ knowledge, awareness, and anti-bullying attitudes, supports the implementation of Child-Friendly School programs, and emphasizes the importance of legal literacy as a practical strategy for preventing bullying in schools.